Use of newer disease-modifying therapies in pediatric multiple sclerosis in the US. (6th November 2018) - Krysko, Kristen M.; Graves, Jennifer; Rensel, Mary; Weinstock-Guttman, Bianca; Aaen, Gregory; Benson, Leslie; Chitnis, Tanuja; Gorman, Mark; Goyal, Manu; Krupp, Lauren; Lotze, Timothy; Mar, Soe; et al.
Abstract : Objective: To characterize the use and safety of newer disease-modifying therapies (DMTs) in children with multiple sclerosis (MS) and clinically isolated syndrome (CIS) treated under 18 years of age. Methods: This is a cohort study including children with MS or CIS followed at 12 outpatient practices participating in the US Network of Pediatric MS Centers. DMT use, including duration, dose, and side effects, was analyzed. Newer DMTs were defined as agents receiving Food and Drug Administration approval or with increased use in adult MS after 2005. Results: As of July 2017, 1, 019 pediatric patients with MS (n = 748) or CIS (n = 271) were enrolled (65% female, mean onset 13.0 ± 3.9 years, mean follow-up 3.5 ± 3.1 years, median 1.6 visits per year). Of these, 78% (n = 587) with MS and 11% (n = 31) with CIS received DMT before 18 years of age. This consisted of at least one newer DMT in 42%, including dimethyl fumarate (n = 102), natalizumab (n = 101), rituximab (n = 57), fingolimod (n = 37), daclizumab (n = 5), and teriflunomide (n = 3). Among 17%, the initial DMT prescribed was a newer agent (36 dimethyl fumarate, 30 natalizumab, 22 rituximab, 14 fingolimod, 2 teriflunomide). Over the last 10 years, the use of newer agents has increased, particularly in those ≥12 years and to lesser extent in those <12 years. The short-term side effect profiles of newer DMTs did not differ from those reported in adults. Conclusion: Newer DMTs are often used in pediatric MS, and have similar short-term safety, tolerability, and side effect profiles as in adults. These findings may help inform pediatric MS management.